The Mediating Role of Perceived Social Support in the Relationship Between Experiential Avoidance and Rumination Among Pregnant Women with Depression - Bagheri, Sara; Ebrahim Sarichloo, Mohammad; Bajelan, Fatemeh; Rotivand Ghiasvand, Zahra; Ghafuori, Azam (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aims to examine whether perceived social support mediates the relationship between experiential avoidance and rumination in pregnant women with depression. Methods and Materials: A descriptive-correlational study using structural equation modeling (SEM) included 250 pregnant women aged 25–35 years diagnosed with depression, recruited from maternal clinics in Tehran, Iran (2019–2020). Participants completed the Beck Depression Inventory-II (BDI-II), the Multidimensional Scale of Perceived Social Support (MSPSS), the Ruminative Response Scale (RRS), and the Acceptance and Action Questionnaire-II (AAQ-II). SEM assessed model fit and mediation effects. Findings: The model showed a good fit (GFI = 0.92, CFI = 0.93, RMSEA = 0.084). Perceived social support partially mediated the relationship between experiential avoidance and rumination (indirect effect: β = 0.45, p < 0.05; direct effect: β = 0.27, p < 0.05). Conclusion: Perceived social support reduces the impact of experiential avoidance on rumination, offering a protective mechanism against perinatal depression. Implications: Midwives should integrate social support interventions, such as peer groups or family counseling, into prenatal care to enhance maternal mental health.